The evaluation system proposal of the businesses preparedness for cooperative management implementation - Vodák, Josef; Soviar, Jakub; Lendel, Viliam (Business: Theory and Practice, 2013)
The objective of the paper is to propose an assessment system of company readiness for cooperative management utilisation according to a detailed analysis of scientific literature and according to a performed empirical research. The proposal defines particular levels of readiness, basic methodology and the way of the readiness index calculation. The paper has brought the application of the proposed assessment system of readiness for cooperative management utilisation in the conditions of Slovak companies according to the empirical research carried out on the sample of 221 respondents.